THEORY OF STATE AND LAW IN REGULATORY BASIS INFORMATION SOCIETY - Калюжний, Ростислав Андрійович; Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
One of the main priorities of Ukraine is striving to build focused on people-centered, open to all and aimed at developing the information society, where everyone could create and accumulate information and knowledge, be it free access, use and share to enable each people to realize their potential, contributing to the social and personal development and improve quality of life. <!--[if gte mso 9]> <![endif]--><span style="font-size: 11.0pt; line-height: 110%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; color: black; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Одним із головних пріоритетів України є прагнення побудувати орієнтоване на інтереси людей, відкрите для всіх і спрямоване на розвиток інформаційне суспільство, в якому кожний міг би створювати і накопичувати інформацію та знання, мати до неї вільний доступ, користуватися і обмінюватися ними, щоб надати можливість кожній людині повною мірою реалізувати свій потенціал, сприяючи суспільному і особистому розвиткові та підвищувати якість життя<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Обычная таблица"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif";} --> <!--[endif] -->